2019
DOI: 10.3390/jcm8111940
|View full text |Cite
|
Sign up to set email alerts
|

First Evaluation of an Index of Low Vagally-Mediated Heart Rate Variability as a Marker of Health Risks in Human Adults: Proof of Concept

Abstract: Multiple studies have demonstrated low vagally-mediated heart rate variability (HRV) being associated with a range of risk factors for heart disease and stroke, including inflammation, hyperglycemia, hyperlipidemia, and hypertension. Yet, no cut point exists that indicates elevated risk. In the present study we sought to identify a cut point-value for HRV that is associated with elevated risk across a range of known risk factors. Methods: A total of 9550 working adults from 19 study sites took part in a health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 37 publications
2
52
0
2
Order By: Relevance
“…Regarding clinical implications, the results of the present work might be relevant for the field of cardiology: Given that HRV has established itself as a biomarker for cardiac health in research [9], recent studies suggest its use as a tool for cardiac risk assessment in clinical practice [8,58]. If clinicians were to use HRV assessments for clinical reasons, they should keep the within-person fluctuations of HRV in naturally-cycling females in mind.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding clinical implications, the results of the present work might be relevant for the field of cardiology: Given that HRV has established itself as a biomarker for cardiac health in research [9], recent studies suggest its use as a tool for cardiac risk assessment in clinical practice [8,58]. If clinicians were to use HRV assessments for clinical reasons, they should keep the within-person fluctuations of HRV in naturally-cycling females in mind.…”
Section: Discussionmentioning
confidence: 92%
“…Next, we assessed the percentage improvement of participants who were able to shift out of a clinically at-risk range of low resting-HRV, as defined empirically 36 . In accordance with these guidelines, we report raw RMSSD HRV scores for interpretation, and note RMSSD HRV is considered a reliable and valid time-series metric of vagally-mediated HRV 33,39 .…”
Section: Hrv-shift For Clinically At-risk Participantsmentioning
confidence: 99%
“…Hence, we predict our compassion intervention will, compared to baseline, increase HRV. As an additional exploratory analysis, we will examine the percentage improvement of participants who move out of a clinical 'at risk' range of HRV when engaged in compassion, as identified in a recent paper which assigned elevated cardiac risk to low resting HRV 36 . We will also assess the degree to which two-weeks of training is sufficient to reduce fears of self-compassion, and we will explore the relationship between HRV and behavioural markers of engagement in compassion training across the two-week self-directed engagement period, as assessed via frequency of accessing the training link.…”
mentioning
confidence: 99%
“…Jarczok et al provided the first evidence that daytime RMSSD below 25 ± 4 ms may be associated with elevated risk across a range of established cardiovascular risk factors [odds ratios (OR) 1.5-3.5]. The study suggested that HRV was robustly associated with a measure of self-rated health than a range of other biomarkers (59). Additional research is needed to validate clinical cut-off values for HRV.…”
Section: Use Of Hrv For Stratifying the Risk Of Strokementioning
confidence: 99%